Preparation of Fluorescent Carbon Dots Composites and Their Potential Applications in Biomedicine and Drug Delivery-A Review - Yaru Chai; Yashan Feng; Kun Zhang; Jingan Li (MDPI AG, 2022)
Carbon dots (CDs), a new member of carbon nanostructures, rely on surface modification and functionalization for their good fluorescence phosphorescence and excellent physical and chemical properties, including small size (<10 nm), high chemical stability, biocompatibility, non-toxicity, low cost, and easy synthesis. In the field of medical research on cancer (IARC), CDs, a new material with unique optical properties as a photosensitizer, are being applied to heating local apoptosis induction of cancer cells. In addition, imaging tools can also be combined with a drug to form the nanometer complex compound, the imaging guidance for multi-function dosage, so as to improve the efficiency of drug delivery, which also plays a big role in genetic diagnosis. This paper mainly includes three parts: The first part briefly introduces the synthesis and preparation of carbon dots, and summarizes the advantages and disadvantages of different preparation methods; The second part introduces the preparation methods of carbon dot composites. Finally, the application status of carbon dot composites in biomedicine, cancer theranostics, drug delivery, electrochemistry, and photocatalysis is summarized.